2002
DOI: 10.1073/pnas.212511599
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid deletions are introduced into the V2 region of gp120 during independent pathogenic simian immunodeficiency virus/HIV chimeric virus (SHIV) infections of rhesus monkeys generating variants that are macrophage tropic

Abstract: Highly pathogenic simian immunodeficiency virus͞HIV chimeric viruses (SHIVs) cause extremely rapid, irreversible, and systemic depletions of CD4 ؉ T lymphocytes in inoculated rhesus monkeys. In the absence of this T cell subset, virus production can be sustained for several months by tissue macrophage. During independent infections of seven animals with uncloned virus stocks, SHIV variants emerged bearing amino acid deletions that affected specific residues of the gp120 V2 loop. Some of these macrophagephase S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…The latter result is in agreement with a previous report showing that CCR5 is the coreceptor used by SIV mac239 for infection of macaque PBMC (26). SHIV DH12R-CL-7 also appears to be exclusively T cell tropic since it was unable to establish spreading infections in alveolar macrophage (13).…”
Section: Vol 78 2004supporting
confidence: 93%
See 1 more Smart Citation
“…The latter result is in agreement with a previous report showing that CCR5 is the coreceptor used by SIV mac239 for infection of macaque PBMC (26). SHIV DH12R-CL-7 also appears to be exclusively T cell tropic since it was unable to establish spreading infections in alveolar macrophage (13).…”
Section: Vol 78 2004supporting
confidence: 93%
“…This result indicated that one or more of the three SHIV DH12R molecular clones conferred the highly pathogenic phenotype. In a follow-up experiment, virus stocks of each clone were prepared in rhesus monkey PBMC as previously described (13) and high doses of each were inoculated individually into three different macaques. Figure 1C shows that only the recipient of SHIV DH12R-CL-7 (inoculum size, 3 ϫ 10 4 50% tissue culture infective doses [TCID 50 ]) experienced the complete depletion of CD4 ϩ T lymphocytes (8 CD4 ϩ T cells/ l of plasma at week 3) typically observed with parental uncloned SHIV DH12R (7,10).…”
Section: Pathogenicity Of Cloned Shivs In Rhesus Monkeysmentioning
confidence: 99%
“…A CD4 ϩ CXCR4 ϩ CCR5 Ϫ CyM T cell line, HSC-F (27), was maintained in RPMI medium 1640 containing 10% FBS. RhM PBMCs were prepared and cultured as described previously (35). For PtM PBMC, a mixture of 95% Ficoll-Paque Plus (GE Healthcare, Piscataway, NJ) and 5% Dulbecco's modified PBS was used as a separation medium.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there is evidence showing that most of the events described in hu-PBL-SCID mice also occur in humans, as well as in primate models of lentiviral infection. Indeed, two recent papers from the same group describe the ability of simian immunodeficiency virus͞HIV type 1 chimera (SHIV)-infected macrophages to induce both virus replication and immunological damage in experimentally infected monkeys (32,33). In addition, the role of macrophages in the pathogenesis of HIV encephalitis has been clearly described in humans and confirmed in experimental models of monkeys and hu-PBL-SCID mice (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%